Writing Matters: Writing-to-Learn Activities Increase Undergraduate Performance in Cell Biology. (2nd May 2018) - Balgopal, Meena M; Casper, Anne Marie A; Wallace, Alison M; Laybourn, Paul J; Brisch, Ellen
Abstract: Biology educators need instructional strategies to improve student learning outcomes, especially in foundational science courses, in which students are presented vast amounts of content. Writing-to-learn (WTL) tasks in lecture courses can help biology students increase performance and use abstract concepts in writing-to-communicate (WTC) tasks. Our WTL interventions included the use of graphic organizers, iterative writing, peer evaluation, and self-evaluation administered in an introductory cell biology course for molecular bioscience majors. We tested three WTL treatments—lots of writing, some writing, and little writing—and compared them with no-writing control sections. We examined the effects of WTL on performance (essay-question grades on exams and total exam scores) and WTC (content analysis). WTL was associated with (a) increased performance, particularly for students identifying as first-generation college students and minorities, and (b) increased use of abstract concepts in WTC tasks over the course of the semester in two WTL interventions.